Manganese(II)‐Mediated Domino Annulation Reaction of Vinyl Azides and 4‐Hydroxycoumarin: A Stereoselective Synthesis of Spirobenzofuranone‐lactams. Issue 19 (12th September 2016) - Guo, Shanshan; Chen, Binhui; Zhao, Donghong; Chen, Wenteng; Zhang, Guolin
Abstract: A manganese(II) acetate‐catalyzed domino reaction of vinyl azides and 4‐hydroxycoumarin has been developed for the synthesis of polyfunctionalized spirofuranone‐lactams. A wide range of vinyl azides are capable of providing the desired spirofuranone‐lactams in good to excellent yields. The reaction was achieved via thermal decomposition of vinyl azides to 2 H ‐azirines, followed by an intramolecular nucleophilic attack and stereoselective cyclization. The mild reaction conditions and easy operation make this reaction advantageous for the synthesis of spirofuranone‐lactams. Abstract :